2019
DOI: 10.5539/jas.v11n17p227
|View full text |Cite
|
Sign up to set email alerts
|

Defoliation Levels Supported in Soybean Crop With No Harm on Productivity in the Municipality of Parauapebas

Abstract: The reduction in the leaf area is one of the causes in the fall in soybean (Glycine max) productivity as it depends on the production of photoassimilates generated by the leaves, so any factor that interferes in its leaf area may affect the production. The attack of defoliating insects is among such factors. They cause a marked drop in grain yield due to its direct action, therefore, reducing the leaf area, consequently reducing the photosynthetic rate of the plant. The agronomic characteristics of the cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…According to Damasceno et al (2019), soybeans have a great capacity to recover from defoliation at early stages of plant development. Significant reductions in grain yield only occur when there is intense defoliation, close to 100%.…”
Section: Resultsmentioning
confidence: 99%
“…According to Damasceno et al (2019), soybeans have a great capacity to recover from defoliation at early stages of plant development. Significant reductions in grain yield only occur when there is intense defoliation, close to 100%.…”
Section: Resultsmentioning
confidence: 99%
“…Plants with this type of growth continue to produce new leaves even after the beginning of flowering (WERNER et al, 2016) and can reach about 70% of their final height throughout the reproductive period. Damasceno et al (2019) found no significant difference in the height of plants subjected to defoliation at different stages and levels; however, these authors observed a greater reduction in height (28% compared to the control treatment, without defoliation), when defoliation was performed at the R5 stage, but the level of defoliation in this treatment was total.…”
Section: Resultsmentioning
confidence: 78%
“…According to Damasceno et al (2019), at the early stages of development, soybean plants have a great capacity for recovery from defoliation. These authors observed no significant reductions in grain yield for defoliation carried out at the early stages of vegetative development, unless there is total defoliation.…”
Section: Resultsmentioning
confidence: 99%